1993
DOI: 10.1101/gad.7.6.986
|View full text |Cite
|
Sign up to set email alerts
|

A G-protein beta-subunit is essential for Dictyostelium development.

Abstract: Recent studies have demonstrated that G-protein-linked signal transduction pathways play a significant role in the developmental program of the simple eukaryotic organism Dictyostelium. We have reported previously the isolation of a G-protein 13-subunit and present here a more complete analysis of this gene. Low-stringency Southern blots and RFLP mapping studies suggest that the 13-subunit is a unique gene found on linkage group If. Its deduced amino acid sequence of 347 residues is -60% identical to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 55 publications
2
102
0
Order By: Relevance
“…Although g␤ Ϫ cells were completely defective in aggregation and most signaling events (Wu et al, 1995), HisG␤/g␤ Ϫ cells developed appropriately into spores and stalks (our unpublished results). The HisG␤ protein was not largely overexpressed, consistent with previous data suggesting tight control of G␤ expression (Lilly et al, 1993). Through purification of HisG␤␥, G␥ was isolated from the membrane fractions of 10 11 cells (Table 1).…”
Section: Purification Of the G␥-subunit And Isolation Of Its Cdnasupporting
confidence: 68%
See 1 more Smart Citation
“…Although g␤ Ϫ cells were completely defective in aggregation and most signaling events (Wu et al, 1995), HisG␤/g␤ Ϫ cells developed appropriately into spores and stalks (our unpublished results). The HisG␤ protein was not largely overexpressed, consistent with previous data suggesting tight control of G␤ expression (Lilly et al, 1993). Through purification of HisG␤␥, G␥ was isolated from the membrane fractions of 10 11 cells (Table 1).…”
Section: Purification Of the G␥-subunit And Isolation Of Its Cdnasupporting
confidence: 68%
“…GTT TTA AAA GAA AAT GAA ACC G C G Approximately 1.5 ϫ 10 5 phages from gt11 cDNA library, prepared from mRNA isolated at 2-4 h of development, were screened (Lilly et al, 1993). Fifty-two positive clones were detected and 4 independent clones were obtained after secondary and tertiary screens.…”
Section: Isolation Of G␥ Cdnamentioning
confidence: 99%
“…Stable expression of a G␤ subunit has been shown to require G␥ to form a G␤␥ dimer (Schmidt and Neer, 1991). Previous studies have demonstrated that the protein level of the D. discoideum G␤ does not change even when its mRNA is overexpressed Ͼ10 fold, presumably because excess G␤ proteins that do not form dimers with G␥ subunits are unstable (Lilly et al, 1993). We demonstrated that each G␤ subunit (SN1-SN5 alleles) was expressed at same level as a wild-type G␤, suggesting that each SN G␤ subunit can associate with a G␥ to form a stable G␤␥ dimer.…”
Section: Discussionmentioning
confidence: 64%
“…The new transformants showed the same characteristics as did the original mutants. To rule out the possibility that the phenotypes of the SN mutants were caused by an inadequate expression of the mutant G␤ subunits, we carried out immunoblot analysis using specific G␤ antiserum (Lilly et al, 1993). As shown in Figure 2, the SN1-SN5 cells expressed G␤ at the same level as wild-type cells, whereas SN6 cells expressed G␤ at a lower level.…”
Section: Isolation Of Sn G␤ Mutationsmentioning
confidence: 99%
See 1 more Smart Citation